COTTON RESIDUE MANAGEMENT IN COTTON-GREEN GRAM CROPPINGSEQUENCE-AN ON FARM EVALUATION - G. RAKESH, G.ESWARA REDDY, Y. BHARATHI, M. VIJAYKUMAR, A. DINESH, N. SWAPNA, M. SAI CHARAN, G. NARENDAR, A. KRISHNA CHAITANYA, M. SRIDHAR; B.BALAJI NAIK (The Journal of Research, PJTSAU, 2026)
An on-farm trial was conducted during Summer 2025 at Ganeshwaram and Bodyathanda villages of Khammam, Telangana, to evaluate the effect of cotton residue management practices on the performance of greengram (MGG-351) under irrigated conditions. The experiment was laid out in an On-Farm Research (OFR) design with three replications across farmer fields, comparing three treatments: T1– incorporation by rotavator, and FP – farmer’s practice (burning of stalks).Results revealed that mechanical incorporation of residues using a incorporation by rotavator (T1) markedly improved growth and yield attributes such as plant height (58.6 cm), clusters per plant (7.0), and pods per cluster (7.0), compared to the farmer’s practice. The treatment recorded a 9.7% higher seed yield (1543 kg/ha) and enhanced haulm yield (3820 kg/ha) over burning (1393 and 3610 kg/ha, respectively). The economic analysis showed higher profitability with net returns of 91,367/ha and a B:C ratio of 2.92:1, surpassing the farmer’s practice ( 75,967/ha; 2.53:1). Post-incorporation soil analysis indicated improvement in organic carbon and microbial activity, confirming the beneficial effect of residue decomposition on soil health. The findings emphasize that mechanical incorporation of cotton residues using shredders is a sustainable, eco-friendly, and economically viable alternative to residue burning. Wider adoption through farmer training and access to shredding machinery can significantly enhance soil productivity and environmental sustainability in cotton–greengram systems.